Nested repetitive structure techniques in examination seating number allocation process at UiTM Pulau Pinang branch / Jamal Othman, Rozita Kadar and Naemah Abdul Wahab - Othman, Jamal; Kadar, Rozita; Abdul Wahab, Naemah (UiTM Cawangan Perlis, 2020)
Preparation of examination seating numbers during the final examination at UiTM Pulau Pinang branch is manually drafted and written by the examination unit staff on the class lists printed through the Student Integrated Managements Systems (SIMs). Process of assigning the seating number for each student takes couple of weeks and this task has become a challenging part for examination unit. Since the students' enrolments are linearly increasing every semester, the workloads among Examination Unit staffs become very burdensome in assigning the seating number. To automate the process of assigning the seating numbers, an algorithm was designed and constructed using the nested repetitive or looping structure techniques with JAVA programming language. Two tasks were identified in assigning the seating numbers; the first task was to set the examination seating number range with start and end numbers for each group of courses registered by the students and the subsequent task was to assign the seating number for each student accordingly by group seating number range as specified during the prior task without the violation or overlapping of seating numbers. The algorithm was tested using real data enrolments taken from SIMs for two semesters and resulted in positive effect especially on the reduction of stressfulness and zero erroneous allocation of the seating numbers.